2012
DOI: 10.3109/09638237.2012.705920
|View full text |Cite
|
Sign up to set email alerts
|

A description and evaluation of a challenging behaviour workshop

Abstract: Building up positive relationships with staff, addressing negative expectations and seeking support from all levels of management are essential in terms of reducing barriers to training in psychiatric settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…This provides a good example of psychological therapists using their clinical skills in an organizational context. The findings from this study and previous research also highlight the essential role that managers play in ensuring the successful uptake and implementation of interventions on a long‐term basis (Berry et al., ; Berry & Haddock, ).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…This provides a good example of psychological therapists using their clinical skills in an organizational context. The findings from this study and previous research also highlight the essential role that managers play in ensuring the successful uptake and implementation of interventions on a long‐term basis (Berry et al., ; Berry & Haddock, ).…”
Section: Discussionsupporting
confidence: 64%
“…However, to facilitate future implementation of formulation, it would be important to identify and engage more resistant staff. The authors’ previous experience suggests that motivational interviewing strategies, including rolling with resistance and identifying staff strengths and skills through positive affirmations, work well in engaging resistant staff members (Berry et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This is an interesting finding since the healthcare system in the UK has moved from mixed to single sex wards. Other interventions, such as challenging behaviour workshops and team reflective practice did not significantly reduce stress or burnout (Berry et al , 2012; Blumenthal et al , 2011).…”
Section: Discussionmentioning
confidence: 92%
“…This is an interesting finding since the healthcare system in the UK has moved from mixed to single sex wards. Other interventions, such as challenging behaviour workshops and team reflective practice did not significantly reduce stress or burnout (Berry et al, 2012;Blumenthal et al, 2011). Howard (2009) found that staff working in a forensic unit had slightly higher levels of emotional exhaustion than those who worked in the community.…”
Section: Effect Of Interventionsmentioning
confidence: 97%
“…These studies suggest that the CIES/WAS might be described as responsive. It should be noted, however, that 2 studies did not detect changes that would theoretically be expected after an intervention designed to improve the quality of staff and patient relationships (change would theoretically be expected because staff-resident interactions are a key part of social climate; Berry et al, 2012) and after residents moved to a new purpose-built building (Long, Langford, Clay, Craig, & Hollin, 2011).…”
Section: Cies/wasmentioning
confidence: 99%